Phytochemical survey and in vitro antibacterial activity of ethnomedicinal plants to treat gastrointestinal ailments in Yobe State, Nigeria - Salihu, Abdallah Muhammad (2021)
Many plants in Yobe State, Nigeria have potentialities in curing many diseases. Rural and urban people made use of medicinal plants as their curative measures with the fact that, conventional drugs are quite expensive as well as contribute to the antimicrobial drug resistance. Abundant chemical constituents played vital roles which enabled the fight against any disease and ailments. This study aim to: Assess the most commonly used plant extracts in curing gastrointestinal ailments across Yobe State, Nigeria; evaluate their antibacterial efficacy against some enteric isolates using disk and well diffusion; determine phenolic and flavonoid contents of these plants extracts (Vachelia nilotica pods extract, Sclerocarya birrea stem (bark) extract, Guiera senegalensis leaves extract and Leptadenia hastata leaves extract) and lastly, determine the bioassay guided fractionating substances of the selected plant stem (bark), and detect compounds present in Sclerocarya birrea (A.Rich.) Hochst stem (bark) fraction capable of actions against the isolate using LC-MS. Thus, a semi structured questionnaires was used to collect initial information on the plants. Their antibacterial efficacy were tested using isolates; Escherichia coli, Salmonella typhi, Bacillus cereus and Staphylococcus aureus, where inhibition zones were measured. Folin-Ciocalteu’s reagent procedure was adopted for the phenolic content, absorbance recorded at 760 nm that of flavonoid measured at 510 nm spectrophotometrically. The data was subjected to Chi-square (x2) comparisons using SPSS version 22 and Graph pad prism version 8. The surveyed plants, were mostly Fabaceae. It has also recorded that 41-50 years were many into practice with their Pvalue 0.13. The majority of the respondents, were illiterates (P-value 0.06). However, ailments were ranged 0.69 – 0.75 informant consensus factors. Moreover, plant species with 0.34, 0.27 values were the highest Relative frequency citations. The (Methanolic and ethanolic) stem (bark) extracts reveal sound inhibition zones; S. typhi (16.3 mm); E. coli (15 mm); B. cereus (17 mm), on crude S. birrea stem (bark) where, 50mg/ml was the MIC without MBC. S. typhi (18 mm); E. coli (15 mm) were inhibited with V. nilotica (L.) Willd. ex Delile pods ethanolic extract, and exerted its MICs on (12.5 and 25 mg/ml & 50mg/ml).Nevertheless, organisms were resistant to aqueous extracts using Ciprofloxacin (19.7 mm - 33 mm) as the positive control, where by, no inhibition zones procured from Leptadenia hastata (Pers.) Decne leaves extracts against the isolates. Extracts were significantly different according to Tukey at p ≥0.05. Nevertheless, Gallic acid increased tremendously in V. nilotica pods extracts with a curve (R2 = 0.9958). While a large Catechin increase noticed in S. birrea stem (bark) extracts and followed by V. nilotica pods extracts with a curve (R2 = 0.9993), all were significantly different at P-value < 0.0001 across the extracts which turned to have low contents especially L. hastata leaves extracts as compared. Their respective correlations were clearly denote phenolic contents with a curve (R2 = 0.5025) and flavonoid contents (R2 = 0.7089). Subsequently, 10mg/ml of the S. birrea stem (bark) ethyl acetate fraction extract was the MIC and no MBC on the fraction extract, therefore, inhibited the growth of the S. typhi. Statistically showed that, the isolate was susceptible to the positive control (Ciprofloxacin 30.33±0.0) as the highest inhibition zone followed by the ethyl acetate fraction extract at 10 mg/ml (9.7 ±0.0) and resistant as well at P< 0.0001 Tukey. Subsequently, LC-HRMS results of the most active fraction identified 16 compounds with various structures include:1,8-Diazabicyclo[5.4.0]undec-7- ene;Epigallocatechingallate;2,Amino1,3,4octadecanetriol;Gentisic acid; Vidarabine as well as DL-Isoleucine among others. Lastly, reasonable amount of chemical compounds determined the actions of individual plants, notably towards development of many valuable pharmaceutical products. S. birrea stem (bark) extract was found to be very useful in Yobe State, which is in accordance with the present study by having very active compounds for the efficacy including Vidarabine as the novel one.